A procedure for electro-elution of DNA from agarose gels - He, M (BioTechniques, 1988)
A simple device is described for efficient and reproducible electro-elution of DNA resolved in agarose gels. DNA (greater than 1 micrograms) is recovered with consistent yields of over 70% into preset elution volumes of 100 to 500 microliters